Amelia Earhart : adventure in the sky - Sabin, Francene; Milone-Dugan, Karen (Mahwah, N.J. : Troll Associates, 1983)
A biography of an aviation pioneer, emphasizing her childhood.
5.1
3-6
Keywords: Earhart, Amelia, -- 1897-1937 -- Juvenile literature; Earhart, Amelia, -- 1897-1937.; Earhart, Amelia, -- 1897-1937.; Air pilots -- United States -- Biography -- Juvenile literature; Air pilots; Air pilots